« Marot y fut » : Le Discours de la court de Claude Chappuys - Preisig, Florian (Renaissance and Reformation / Renaissance et Réforme, 2013)
In 1543 Claude Chappuys published Le Discours de la court, a long poem in praise of the court of Francis I. This text, a hybrid of moral allegory and enumerative discourse, recalls themes, structures, and poetic language that can be found in Guillaume de Lorris, Jean Lemaire de Belges, and above all, as I will argue, Marot, with whom Chappuys had collaborated earlier, for example in the context of the Blasons anatomiques du corps féminin. Yet at the same time, and more importantly, this article demonstrates that Chappuys’s poem, despite its non-controversial tone, can be read as an implicit rejection of key aspects of Marot’s heritage. Indeed, Chappuys condemns Marot’s polemical vein indirectly through the negative depiction of the Pasquin-L’Arétin duo, a clear figure of the satirical genre, and through veiled allusions to L’Enfer and the coq-à-l’âne poems. This presence of Marot in the intertext of an extremely consensual work written for Francis I is all the more significant when one remarks that the Discours was published just a few months after Marot’s flight to Geneva, in a renewed context of interconfessional tension; it constitutes, so to say, the poem’s flipside. Symptomatically, the only direct mention of Marot in the Discours is laconic, "Marot was here," and can be read in different ways. This article can be seen as a discussion of this short phrase and its resonances, with special attention given to its specific location in the carefully elaborated catalogue of the court that makes up the second half of the work. Generally speaking, the following offers an introduction to Chappuys’ poem and attempts to rehabilitate a work that has been neglected or read primarily in a political perspective.